Post-glacial phylogeography and evolution of a wide-ranging highly-exploited keystone forest tree, eastern white pine (Pinus strobus) in North America: single refugium, multiple routes - Zinck, John W. R. (BMC Evol Biol, 2016)
BACKGROUND: Knowledge of the historical distribution and postglacial phylogeography and evolution of a species is important to better understand its current distribution and population structure and potential fate in the future, especially under climate change conditions, and conservation of its genetic resources. We have addressed this issue in a wide-ranging and heavily exploited keystone forest tree species of eastern North America, eastern white pine (Pinus strobus). We examined the range-wide population genetic structure, tested various hypothetical population history and evolutionary scenarios and inferred the location of glacial refugium and post-glacial recolonization routes. Our hypothesis was that eastern white pine survived in a single glacial refugium and expanded through multiple post-glacial recolonization routes. RESULTS: We studied the range-wide genetic diversity and population structure of 33 eastern white pine populations using 12 nuclear and 3 chloroplast microsatellite DNA markers. We used Approximate Bayesian Computation approach to test various evolutionary scenarios. We observed high levels of genetic diversity, and significant genetic differentiation (F(ST) = 0.104) and population structure among eastern white pine populations across its range. A south to north trend of declining genetic diversity existed, consistent with repeated founder effects during post-glaciation migration northwards. We observed broad consensus from nuclear and chloroplast genetic markers supporting the presence of two main post-glacial recolonization routes that originated from a single southern refugium in the mid-Atlantic plain. One route gave rise to populations at the western margin of the species’ range in Minnesota and western Ontario. The second route gave rise to central-eastern populations, which branched into two subgroups: central and eastern. We observed minimal sharing of chloroplast haplotypes between recolonization routes but there was evidence of admixture between the western and west-central populations. CONCLUSIONS: Our study reveals a single southern refugium, two recolonization routes and three genetically distinguishable lineages in eastern white pine that we suggest to be treated as separate Evolutionarily Significant Units. Like many wide-ranging North American species, eastern white pine retains the genetic signatures of post-glacial recolonization and evolution, and its contemporary population genetic structure reflects not just the modern distribution and effects of heavy exploitation but also routes northward from its glacial refugium. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12862-016-0624-1) contains supplementary material, which is available to authorized users.